Рішення Європейського суду з прав людини як індікатор зовнішньополітичної електоральної легітимації влади на пострадянському просторі. - Юрійчук, Є.П.; Юрийчук, Е.П.; Jurijchuk, E. (My University, 2012)
The author traces the dynamics of appeals to the Court depending on the electoral cycles and the legal culture of the population and the type of political culture, analyzes the nature of violations of fundamental ele- ments of electoral and other related, political rights, it turns out the attitude of govern ments seeking legitimacy for international level, the European Court as an indicator of electoral legitimacy.
Юрійчук Є.П. Рішення Європейського суду з прав людини як індікатор зовнішньополітичної електоральної легітимації влади на пострадянському просторі. / Є.П.Юрійчук //Актуальні проблеми політики : зб. наук. пр. / гол. ред. С. В. Ківалов ; відп. за вип. Л. І. Кормич. – Одеса : Національний університет "Одеська юридична академія" : Південноукраїнський центр гендерних проблем, 2012. – Вип. 44. – C. 170 - 181.
Keywords: Європейський суд як індикатор електоральної легітимації; Рішення Європейського суду з прав людини; Легітимація влади на пострадянському просторі; Європейський суд; Эвропейский суд; Легитимация власти в постсоветском пространстве; Решения Эвропейского суда по правам человека; Эвропейский суд как индикатор электоральной легитимации; The level of international court as an indicator of electoral legitimation; Decisions of the level of international Court of Human Rights; The legitimization of power in post-Soviet space; The European court